2018
DOI: 10.1590/fst.22117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activities, total phenolic content (TPC), and total catechin content (TCC) of 10 sugar apple (Annona squamosa L.) cultivar peels grown in Thailand

Abstract: Antioxidant activities, total phenolic content (TPC), and total catechin content were analyzed in the ethanol extracts of 10 sugar apple (Annona squamosa L.) cultivar peels grown in Thailand. Antioxidant activity assays carried out in the this study were the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, ferric ion reducing antioxidant power (FRAP), 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation scavenging activity, and oxygen radical absorbance activity (DRAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
8
1
1
Order By: Relevance
“…With regards to seed and pulp portions, African pride had the highest phenolic content (1.40 ± 0.07 mg GAE/g and 3.81 ± 0.17 mg GAE/g, respectively) when compared to the other varieties. Previously, Manochai et al [5] reported values that range between 33.8 and 140.4 mg GAE/g, where the African pride showed higher values than those found in our study. The variation in the concentration of total phenolics in the custard apple might be due to the different concentrations of solvents used for extraction [24].…”
Section: Phenolic Content Estimation (Tfc Tfc Ttc)contrasting
confidence: 68%
See 2 more Smart Citations
“…With regards to seed and pulp portions, African pride had the highest phenolic content (1.40 ± 0.07 mg GAE/g and 3.81 ± 0.17 mg GAE/g, respectively) when compared to the other varieties. Previously, Manochai et al [5] reported values that range between 33.8 and 140.4 mg GAE/g, where the African pride showed higher values than those found in our study. The variation in the concentration of total phenolics in the custard apple might be due to the different concentrations of solvents used for extraction [24].…”
Section: Phenolic Content Estimation (Tfc Tfc Ttc)contrasting
confidence: 68%
“…Correlations between ABTS radical scavenging activity and total antioxidant capacity were found to be highly interrelated in our research. Manochai et al [5] reported a strong correlation between TPC and ABTS radical scavenging activity and ferric reducing ability of plasma with r 2 values of 0.958 (p < 0.01) and 0.995 (p < 0.01), respectively, when analyzing the peel of 10 sugar apples. Nam et al [43] obtained a negative correlation between DPPH radical scavenging activity, TPC and other antioxidant activities in pawpaw, and their results were similar to our study.…”
Section: Correlation Between Antioxidant Assays and Phenolic Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the existence of a correlation between total phenolic content and antioxidant capacity has been reported by several authors [ 21 , 22 , 23 ]. According to the results obtained, it is possible to verify this relation in the PCA, in which the fractions that presented high total content of polyphenols also presented a high capacity of radical DPPH reduction.…”
Section: Resultsmentioning
confidence: 86%
“…In a recent research, 10 sugar apple (Annona squamosa L.) cultivar peels from Thailand were evaluated. The content of antioxidants was notably lower (ranging from 0.4 to 32 mg/kg) [57] than these obtained to the inajá pulp (181.9 mg/kg), and higher to the biribá pulp (<LOD) which belongs to the same botanic family. The inajá pulp showed a different stilbenes profile highlighting the resveratrol content, which inhibits the formation of free radicals and has antimutagenic activity [58].…”
Section: Sift Deskmentioning
confidence: 57%